A review of split-cycle engines. (August 2020) - Finneran, Joshua; Garner, Colin P; Bassett, Michael; Hall, Jonathan
This article reviews split-cycle internal combustion engine designs. The review includes historical work, assessment of prototypes and discussion of the most recent designs. There has been an abundance of split-cycle engine designs proposed since the first in 1872. Despite this, very few prototypes exist, and no split-cycle engines are reported to be in series production. The few split-cycle prototypes that have been developed have faced practical challenges contributing to limited performance. These challenges include air flow restrictions into the expansion cylinder, late combustion, thermal management issues, and mechanical challenges with the crossover valve actuation mechanism. The main promoted advantage of split-cycle engines is the increased thermal efficiency compared to conventional internal combustion engines. However, an efficiency improvement has not thus far been demonstrated in published test data. The thermodynamic studies reviewed suggest that split-cycle engines should be more efficient than conventional four-stroke engines. Reasons why increased thermal efficiency is not realised in practice could be due to practical compromises, or due to inherent architectural split-cycle engine design limitations. It was found that the number of split-cycle engine patents has increased significantly over recent years, suggesting an increased commercial interest in the concept since the possibility of increased efficiency becomes more desirable and might outweigh the drawbacks of practical challenges.